2020
DOI: 10.1186/s12879-020-05500-x
|View full text |Cite
|
Sign up to set email alerts
|

The burden of typhoid fever in Klang Valley, Malaysia, 2011–2015

Abstract: Background Typhoid fever causes global morbidity and mortality and is a significant health burden, particularly in low- and middle-income countries. The direct fecal-oral route is the main transmission mode, but indirect environmental transmission could occur, particularly in urban settings. This study aimed to investigate the burden and trend of typhoid fever, reporting the coverage system between government and private practice and pattern of multidrug-resistant (MDR) typhoid cases in the urban Klang Valley … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…Although there is concern about the increasing number of multidrug-resistant Salmonella Typhi isolated globally, local data in Malaysia showed that this isolate occurred in only 7.5% of Salmonella Typhi and the highest resistance rate was found in ciprofloxacin with 24.1% (Muhammad et al, 2020). The ceftriaxone which is the first line of antimicrobial used in Salmonella Typhi infection had a very low resistance rate at 1.6% (Muhammad et al, 2020). The bacterial isolate from our patient was sensitive to all the tested antibiotics.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Although there is concern about the increasing number of multidrug-resistant Salmonella Typhi isolated globally, local data in Malaysia showed that this isolate occurred in only 7.5% of Salmonella Typhi and the highest resistance rate was found in ciprofloxacin with 24.1% (Muhammad et al, 2020). The ceftriaxone which is the first line of antimicrobial used in Salmonella Typhi infection had a very low resistance rate at 1.6% (Muhammad et al, 2020). The bacterial isolate from our patient was sensitive to all the tested antibiotics.…”
Section: Discussionmentioning
confidence: 57%
“…Thus, improvement in microbiologic quality of drinking water and better sanitation system leads to a reduction in typhoid fever incidence (Crump, 2019). The latest epidemiological study in Malaysia which was conducted in the most developed state in the country showed the peak incidence of 1.42 cases per 100,000 population in 2015 (Muhammad et al, 2020). Nevertheless, typhoid fever is still being reported particularly in the endemic area and the neuropsychiatric manifestation of typhoid fever continued to be reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typhoid disease is rare in developed countries, but still prevalent in certain areas of developing countries with limited access to clean water and poor sanitation [ 42 , 43 ]. In Malaysia, it was estimated that 0.5 to 0.7 confirmed cases of Salmonella infection per 100,000 population were reported in 2015 [ 44 ]. Even though most of the outbreaks are endemic, the cases of both typhoid and paratyphoid fever declined globally by 45% from the year 1990 to 2017.…”
Section: Salmonella and Their Related Diseasesmentioning
confidence: 99%
“…In Malaysia, recent estimates suggest that approximately 0.58 to 1.42 cases of S . Typhi infection per 100,000 population were reported each year between 2011 and 2015 and most of the cases were due to travelers returning from an endemic region, migrants and food chains being contaminated by food handlers [ 3 ].…”
Section: Introductionmentioning
confidence: 99%